Growing up Bank Street : a Greenwich Village memoir - Florio, Donna, 1955- (Book collections on Project MUSE., 2021)
A vivid memoir of life in one of New York City's most dynamic neighborhoodsGrowing Up Bank Street is an evocative, tender account of life in Greenwich Village, on a unique street that offered warmth, support, and inspiration to an adventurous and openhearted young girl. Bank Street, a short strip of elegant brownstones and humble tenements in Greenwich Village, can trace its lineage back to the yellow fever epidemics of colonial New York. In the middle of the last century, it became home to a cast of extraordinary characters whose stories intertwine in this spirited narrative. Growing up, Donna Florio had flamboyant, opera performer parents and even more free-spirited neighbors. As a child, she lived among beatniks, artists, rock musicians, social visionaries, movie stars, and gritty blue-collar workers, who imparted to her their irrepressibly eccentric life rules. The real-life Auntie Mame taught her that she is a divine flame from the universe. John Lennon, who lived down the street, was gracious when she dumped water on his head. Sex Pistol star Sid Vicious lived in the apartment next door, and his heroin overdose death came as a wake-up call during her wild twenties. An elderly Broadway dancer led by brave example as Donna helped him comfort dying Villagers in the terrifying early days of AIDS, and a reclusive writer gave her a path back from the brink when, as a witness to the attacks of 9/11, her world collapsed. These vibrant vignettes weave together a colorful coming of age tale against the backdrop of a historic, iconoclastic street whose residents have been at the heart of the American story. As Greenwich Village gentrifies and the hallmarks of its colorful past disappear, Growing Up Bank Street gives the reader a captivating glimpse of the thriving culture that once filled its storied streets.